Characterization of soil pathogenic fungi in the rhizosphere of siwalan palm (Borassus flabellifer L.) - Nurtjahyani, Supiana Dian; Sulistyaningrum, Heny; Sulistiono; Amin, Mochamad; Tegar Kurnia, Dwi; Dhiaulhaq, M. Rafi; Mustofa, Ali (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Soil-borne fungal pathogens represent a persistent threat to plant health due to their ability to colonize the rhizosphere and infect root systems, yet information on their diversity in non-industrial palm species remains limited. Siwalan (Borassus flabellifer L.) is a drought-tolerant palm of ecological and socio-economic importance, but its rhizospheric fungal communities have not been systematically characterized. This study aimed to (1) isolate soil-borne fungi from the rhizosphere of siwalan and (2) identify potential pathogenic fungi based on macroscopic and microscopic morphological characteristics. Rhizosphere soil samples were collected at depths of 5–20 cm and processed using the soil dilution plate method. Fungal isolates were cultured on potato dextrose agar (PDA), purified through subculturing, and identified using colony morphology and microscopic structures observed through slide culture and lactophenol cotton blue staining. Data were analyzed descriptively by comparing fungal traits with standard taxonomic determination keys. Five soil-borne fungal taxa were successfully isolated and identified, namely Aspergillus flavus, Trichoderma longibrachiatum, Aspergillus oryzae, Aspergillus caelatus, and Aspergillus niger. The isolates exhibited distinct differences in colony pigmentation, growth rate, hyphal structure, vesicle morphology, and conidial characteristics. Among them, A. niger showed the fastest radial growth and highest sporulation intensity, whereas T. longibrachiatum and A. oryzae exhibited relatively slower growth. These morphological variations indicate functional diversity and differing adaptive strategies among fungi inhabiting the siwalan rhizosphere. This study provides the first systematic morphological baseline of soil-borne fungi associated with the rhizosphere of B. flabellifer. The findings contribute novel information on fungal diversity in an underexplored palm species and highlight the importance of early fungal characterization as a foundation for future molecular identification, pathogenicity testing, and the development of sustainable disease management strategies for siwalan cultivation systems.